Izin Poligami di Pengadilan Agama (Suatu Tinjauan Filosofis) - Azni Azni (Jurnal Dakwah Risalah, 2015)
The existence of laws which regulating the polygamy permit means to give shape to public order, to give protection and law guaranty toward rights and obligations of regulational relationships. In addition, to protect the rights of all people. So, the formal conditions of polygamy will care to yudicially getting marriage goals. Therefore, the permit to polygamy phylosophically makes marriage goals reach and educates the public in order to regulations aware.